Mortality Among People With HIV Treated for Tuberculosis Based on Positive, Negative, or No Bacteriologic Test Results for Tuberculosis: The IeDEA Consortium. (10th January 2020) - Humphrey, John M; Mpofu, Philani; Pettit, April C; Musick, Beverly; Carter, E Jane; Messou, Eugène; Marcy, Olivier; Crabtree-Ramirez, Brenda; Yotebieng, Marcel; Anastos, Kathryn; Sterling, Timothy R; Yiannoutsos, Constantin; et al.
Abstract: Background: In resource-constrained settings, many people with HIV (PWH) are treated for tuberculosis (TB) without bacteriologic testing. Their mortality compared with those with bacteriologic testing is uncertain. Methods: We conducted an observational cohort study among PWH ≥15 years of age initiating TB treatment at sites affiliated with 4 International epidemiology Databases to Evaluate AIDS consortium regions from 2012 to 2014: Caribbean, Central and South America, and Central, East, and West Africa. The exposure of interest was the TB bacteriologic test status at TB treatment initiation: positive, negative, or no test result. The hazard of death in the 12 months after TB treatment initiation was estimated using a Cox proportional hazard model. Missing covariate values were multiply imputed. Results: In 2091 PWH, median age 36 years, 53% had CD4 counts ≤200 cells/mm 3, and 52% were on antiretroviral therapy (ART) at TB treatment initiation. The adjusted hazard of death was higher in patients with no test compared with those with positive test results (hazard ratio [HR], 1.56; 95% confidence interval [CI], 1.08–2.26). The hazard of death was also higher among those with negative compared with positive tests but was not statistically significant (HR, 1.28; 95% CI, 0.91–1.81). Being on ART, having a higher CD4 count, and tertiary facility level were associated with a lower hazard for death. Conclusions: There was some evidence that PWH treated for TB with no bacteriologic test results were at higher risk of death than those with positive tests. Research is needed to understand the causes of death in PWH treated for TB without bacteriologic testing.